A Preliminary Framework for Expediting Energy Efficiency Retrofits (EERs) Using Alternative Financing in Indonesian Cities - Bramono, Novi Triadi Iman; Kim, Amy; Berawi, Mohammed Ali (Universitas Indonesia, 2019)
Existing buildings have a huge opportunity in terms of energy and water savings potential in Indonesia. In Jakarta alone, it is estimated that least 90 percent of total buildings were built before 2014. The general perception of having a more energy-efficient existing building is associated with a higher upfront cost and how to finance it. To overcome these issues, incentives have been considered as one important pull factor to implement energy efficiency retrofits (EERs). To identify types of incentive that might work in Indonesia city context, it is important to develop a framework that can be adopted nationally. This research aims to identify the key factors that can be integrated into the framework. To do that, an extensive electronic literature review, added with archival study and case studies analysis using Jakarta as a model for Indonesian cities in implementing green building code. A comprehensive analysis of favorable policy, existing building stock data, study on possible incentive mechanism and added with case studies are presented. From the analysis, it is concluded existing supporting policy, potential energy savings from existing building stock and local capacity are equally important factors. It is expected that these findings will be utilized as the key factors for developing a framework on expediting EERs to be adopted in Indonesia cities, which is an important key to untap the potential energy savings from existing building stock.